In‐office treatment of nasal valve obstruction using a novel, bipolar radiofrequency device. Issue 2 (4th February 2019) - Jacobowitz, Ofer; Driver, Mark; Ephrat, Moshe
Abstract : Objectives: To assess the safety and effectiveness of in‐office bipolar radiofrequency treatment of nasal valve obstruction Study Design: Prospective, nonrandomized, multicenter case series Methods: Adult patients with a Nasal Obstruction Symptom Evaluation scale (NOSE) score ≥60 were selected. Patients were clinically diagnosed with dynamic or static internal nasal valve obstruction as primary or significant contributor to obstruction and were required to have a positive response to nasal mechanical dilators or lateralization maneuvers. Bilateral radio‐frequency treatment was applied intranasally using a novel device, under local anesthesia in a single session. Safety and tolerance were assessed by event reporting, inspection, and Visual Analogue Scale (VAS) for pain. Efficacy was determined using the NOSE score and patient‐reported satisfaction survey at 26 weeks. Results: Fifty patients were treated. No device or procedure‐related serious adverse events occurred. Soreness, edema, and crusting resolved by 1 month. The mean baseline NOSE score was 79.9 (SD 10.8, range 60–100), and all had severe or extreme obstruction. At 26 weeks, mean NOSE score was 69% lower at 24.7 ( P < .0001) with 95% two‐sided confidence intervals 48.5 to 61.1 for decrease. The decrease in NOSE score did not differ significantly between patients who did or did not have prior nasal surgery. Patient satisfaction mean by survey was 8.2 of 10. Conclusion: In office treatment of internal nasal valve obstruction using a bipolar radiofrequency device is safe and well‐tolerated. Nasal obstruction, as assessed using the NOSE questionnaire at 26 weeks, was markedly improved with high patient satisfaction. Level of Evidence: 2b, prospective cohort